ANALYSIS OF THE SA'O ATALAKI TRADITIONAL HOUSE, ENDE REGENCY IN A GEOGRAPHICAL SPATIAL PERSPECTIVE - Dentiana Rero; Enok Maryani (Universitas Negeri Medan, 2022)
Indonesia is one of the countries in the world with various kinds of cultural diversity and different customs. Culture and traditions are formed due to several factors, one of which is geographical factors. Along with the development of the times, culture and customs have an essential role in creating the spatial structure. The spatial frame formed in each region will vary according to the ordinary conditions of the community in carrying out life. A spatial pattern influenced by geographical factors is the Sa'o Atalaki house, located in the Wolotopo traditional village, Ende Regency, East Nusa Tenggara. This study examines the spatial pattern of the Sa'o Atalaki traditional house and its relationship to geographic spatial patterns. This research uses a descriptive analysis method with literature study and direct observation. The study results are the spatial pattern of the Sa'o Atalaki traditional house consisting of several parts that function as a burial place, a deliberation room, and a traditional offering room for ancestors. Meanwhile, spatial planning in geography is divided into no parts, namely spatial, spatial ecology, and spatial complex. The spatial arrangement of traditional houses and geography is made according to the needs of each spatial function, as well as social and environmental impacts. Keywords: Traditional House, Spatial, Sa'o Atalaki, Geographical Spatial, Ende Regency